2023
DOI: 10.1037/sgd0000561
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social group prejudice and vulnerability to sexual violence in bisexual women.

Abstract: Researchers have consistently found an increased vulnerability to sexual violence in bisexual women. Much like the broader literature around sexual violence against women, the limited research examining this vulnerability in bisexual women has focused on intraindividual victim factors such as alcohol use, mental health, and previous sexual assault victimization. Sexual violence researchers are expanding their purview to include sociocultural factors manifested in the immediate context of sexual violence perpet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Cisgender bisexual women’s experiences of sexual violence based on intersecting identities as women and bisexual are shaped by systems of privilege and oppression (Bowleg, 2012; Crenshaw, 1989), including sexism, heterosexism, and monosexism, as well as the specific manifestations of antibisexual stigma, which influence vulnerability to sexual violence (Flanders et al, 2021; Grove & Johnson, 2022) and to negative outcomes in the aftermath (Johnson & Grove, 2017; Salim et al, 2021). Thus, future research on bisexual people’s health outcomes in relation to victimization and minority stress should aim to recruit more diverse samples as systems of power and privilege leave those with marginalized identities most at risk for sexual violence (McCauley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cisgender bisexual women’s experiences of sexual violence based on intersecting identities as women and bisexual are shaped by systems of privilege and oppression (Bowleg, 2012; Crenshaw, 1989), including sexism, heterosexism, and monosexism, as well as the specific manifestations of antibisexual stigma, which influence vulnerability to sexual violence (Flanders et al, 2021; Grove & Johnson, 2022) and to negative outcomes in the aftermath (Johnson & Grove, 2017; Salim et al, 2021). Thus, future research on bisexual people’s health outcomes in relation to victimization and minority stress should aim to recruit more diverse samples as systems of power and privilege leave those with marginalized identities most at risk for sexual violence (McCauley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…At the relationships level, general vulnerability factors such as sexual encounters involving substance or alcohol use (Flack et al, 2015 ; Tyler et al, 2017 ), and affiliation with deviant peer groups (Bhochhibhoya et al, 2021 ), have been associated with increased risk for violence among SOGD. Group-specific factors at the relationship level have also been identified including discordance in outness (Balsam & Szymanski, 2005 ), and experiencing social prejudice and discrimination based on sexual orientation (Grove & Johnson, 2022 ). For instance, results from a cross-sectional study conducted among 133 bisexual women found that women experiencing hostile sexism or biphobia from their peers were more likely to report prior sexual victimization (Grove & Johnson, 2022 ).…”
Section: Sexual Violence Prevalence In the Sogd Communitiesmentioning
confidence: 99%
“…Group-specific factors at the relationship level have also been identified including discordance in outness (Balsam & Szymanski, 2005 ), and experiencing social prejudice and discrimination based on sexual orientation (Grove & Johnson, 2022 ). For instance, results from a cross-sectional study conducted among 133 bisexual women found that women experiencing hostile sexism or biphobia from their peers were more likely to report prior sexual victimization (Grove & Johnson, 2022 ). Some relationships risk factors which are general might be especially elevated among specific SOGD groups.…”
Section: Sexual Violence Prevalence In the Sogd Communitiesmentioning
confidence: 99%
“…The second category includes stereotypes of bisexual people as sexually irresponsible and hypersexual. Bisexual women are highly eroticized and sexually objectified due to sexual irresponsibility stereotypes (Serpe et al, 2020) and this unique sexual stigma heightens the risk for SV (Grove & Johnson, 2023). Sexual stigma and SV are interrelated factors explaining mental health disparities among bisexual women (Flanders et al, 2023).…”
Section: Sexual Violence and Suicide Riskmentioning
confidence: 99%
“…Chen et al, 2020). Not only is SV alarmingly common for bisexual women; it is also intertwined with bisexual minority stress (Grove & Johnson, 2023). Given the sexual objectification and hypersexuality stereotypes experienced by bisexual women, we hypothesized that SV may relate to internal minority stress.…”
Section: Hypothesis 1: Antibisexual Stigmamentioning
confidence: 99%